2013
DOI: 10.1126/science.1230767
|View full text |Cite
|
Sign up to set email alerts
|

A Clock Directly Linking Time to a Particle's Mass

Abstract: Historically, time measurements have been based on oscillation frequencies in systems of particles, from the motion of celestial bodies to atomic transitions. Relativity and quantum mechanics show that even a single particle of mass m determines a Compton frequency ω(0) = mc(2)/[formula: see text] where c is the speed of light and [formula: see text] is Planck's constant h divided by 2π. A clock referenced to ω(0) would enable high-precision mass measurements and a fundamental definition of the second. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
163
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(171 citation statements)
references
References 27 publications
8
163
0
Order By: Relevance
“…Using multiphoton Bragg diffraction [4,5] and simultaneous operation of conjugate interferometers [6], the phase difference has been increased to Φ = 16n 2 ω r T (where the factor of 16 arises from taking the phase difference of the two interferometers), and Earth's gravity and vibrations have been canceled. Unfortunately, however, Bragg diffraction causes a diffraction phase [2, 7-9], which has been the largest systematic effect in high-sensitivity atom interferometers using this technique [2]. Here, we study the diffraction phase in detail and show that it can be suppressed and even nulled by introducing Bloch oscillations as shown in Fig.…”
mentioning
confidence: 87%
“…Using multiphoton Bragg diffraction [4,5] and simultaneous operation of conjugate interferometers [6], the phase difference has been increased to Φ = 16n 2 ω r T (where the factor of 16 arises from taking the phase difference of the two interferometers), and Earth's gravity and vibrations have been canceled. Unfortunately, however, Bragg diffraction causes a diffraction phase [2, 7-9], which has been the largest systematic effect in high-sensitivity atom interferometers using this technique [2]. Here, we study the diffraction phase in detail and show that it can be suppressed and even nulled by introducing Bloch oscillations as shown in Fig.…”
mentioning
confidence: 87%
“…T he development of atom interferometry over the last two decades has given rise to new insights into the tenets of quantum mechanics 1 as well as to ultra-high accuracy sensors for fundamental physics [2][3][4] and technological applications 5,6 . Examples range from the creation of momentum state superpositions by accurate momentum transfer of laser photons 7,8 allowing high precision measurements of rotation, acceleration and gravity 5,6,9,10 , to the splitting of trapped ultracold atoms by local potential barriers [11][12][13] allowing the investigation of fundamental properties of quantum systems of a few or many particles, such as decoherence and entanglement [14][15][16] .…”
mentioning
confidence: 99%
“…This may sound absurd at first, as the Planck mass is so much larger than any known particle. However, recent research has indicated that mass at a deeper level can be seen as a Compton clock [26,27]. This suggests that the Planck mass is related to the Planck time [28], and instead of looking for a very large mass (compared to any observed particle), we should be looking for a very small mass, approximately 1.17 × 10 −51 kg.…”
Section: Mcculloch-heisenberg Newton Equivalent Gravitymentioning
confidence: 99%